AN ECONOMIC STUDY OF THE PRODUCTION AND CONSUMPTION OF DATES IN IRAQ AND ITS IMPACT ON IMPROVING THE EFFICIENCY OF THE USE OF ECONOMIC RESOURCES - Ayyed Jasym Abbood (Scholar Express Journals, 2025)
The production of dates is a source of food and raw materials for many manufacturing industries, making them important crops in terms of food and economy and their role in increasing the efficiency of the use of economic resources. The agricultural sector in Iraq is one of the major sources for the provision of raw materials in many manufacturing industries. The study used a longitudinal data collection method to investigate some of the factors influencing the production of date varieties grown in Iraq. The proper model for the nature of these data was adopted, and an analysis of the integration of the variables included in the study was carried out in order to meet the research's goals. The most significant of the research's findings was that, despite not reaching the level of ambition, date production is still progressing. Since the price of dates is a significant factor that influences their production, price fluctuations are the cause of this slow development. Thus, the study suggested that in order to incentivize farmers to boost production and establish export channels to enable the export of excess overseas, a fixed price level for this crop should be maintained.
Keywords: Date production; Date consumption; Efficiency of economic resource use